2013
DOI: 10.1002/9780470559277.ch130102
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin‐Binding Protein Imaging Probes

Abstract: Penicillin‐binding proteins (PBPs) are membrane‐associated proteins involved in the biosynthesis of peptidoglycan (PG), the main component of bacterial cell walls. These proteins were discovered and named for their affinity to bind the β‐lactam antibiotic penicillin. The importance of the PBPs has long been appreciated; however, the apparent functional redundancy of the ∼5 to 15 proteins that most bacteria possess makes determination of their individual roles difficult. Existing techniques to study PBPs are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…There also appears to be strain-to-strain variability. More recently, fluorescent ␤-lactams have been used to detect PBPs in living cells (25,26). Taking advantage of this advance, we investigated the selectivity profiles of numerous ␤-lactams for the PBPs in live E. coli strains using fluorescent penicillin (Boc-FL) as the readout probe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There also appears to be strain-to-strain variability. More recently, fluorescent ␤-lactams have been used to detect PBPs in living cells (25,26). Taking advantage of this advance, we investigated the selectivity profiles of numerous ␤-lactams for the PBPs in live E. coli strains using fluorescent penicillin (Boc-FL) as the readout probe.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, nonradioactive ␤-lactams have been utilized to examine PBP inhibition and activity (23,24). In particular, fluorescent ␤-lactams, such as Bocillin-FL (Boc-FL; penicillin V conjugated to BODIPY FL dye), have enabled visualization of PBPs in live cells (25,26). With this tool in hand, we sought to examine 22 commercially available ␤-lactams in E. coli to assess their PBP selectivity in live cells.…”
mentioning
confidence: 99%
“…Our recent study using superresolution microscopy revealed that PBP2x of S. pneumoniae is directed to a discrete location separate from PBP2b and PBP1a within the septal aperture during the later stages of cell division (12). Selective fluorescent ␤-lactam chemical probes would provide further insight by visualization of the TP activity of PBPs at different stages of bacterial cell division (25,26).…”
mentioning
confidence: 99%
“…More recently, nonradioactive ␤-lactams, such as fluorescent derivatives, have been used to detect PBPs in both gel-based analyses (23,24) and localization studies in live cells (25,26). Previous PBP profiling with ␤-lactams was performed with the laboratory strains R36A and R6 (10,22,27,28).…”
mentioning
confidence: 99%
“…3b) and demonstrated that they selectively label a small subset of PBPs in B. subtilis and Streptococcus pneumoniae . Fluorescence imaging with 3D-SIM indicated that tagged PBPs localized at the division site in both organisms 45,46 . Dual labeling experiments were performed by incubating whole cells with Ceph C-T to label Ceph C–sensitive PBPs, and then BOCILLIN FL was applied to saturate the remainder of the PBPs, enabling simultaneous analysis of two PBP subsets.…”
Section: Antibiotic-inspired Chemical Probesmentioning
confidence: 99%